The Link Between Emotional Awareness and Interpersonal Sensitivity: The Mediating Role of Alexithymia - Atashpour, Seyed Hamid; Atashpour, Seyed Salar; Atashpour, Samieh Sadat (Journal of Personality and Psychosomatic Research (JPPR), 2025)
This study aimed to investigate the relationship between emotional awareness and interpersonal sensitivity, focusing on the mediating role of alexithymia among adults in Egypt. The research employed a descriptive correlational design with a sample of 390 adult participants selected based on Morgan and Krejcie’s sample size table. Participants were recruited from various Egyptian communities and completed standardized questionnaires measuring emotional awareness, alexithymia, and interpersonal sensitivity. Data analysis was conducted using SPSS-27 for Pearson correlation analysis and AMOS-21 for Structural Equation Modeling (SEM) to examine the proposed mediation model. Model fit was assessed using key indices including Chi-square/df, CFI, TLI, GFI, and RMSEA. Results indicated a significant negative correlation between emotional awareness and interpersonal sensitivity (r = –.47, p < .01), and a significant positive correlation between alexithymia and interpersonal sensitivity (r = .59, p < .01). Emotional awareness also showed a significant negative correlation with alexithymia (r = –.54, p < .01). SEM results confirmed that emotional awareness significantly predicted lower alexithymia (β = –.54, p < .001), which in turn significantly predicted higher interpersonal sensitivity (β = .59, p < .001). The direct path from emotional awareness to interpersonal sensitivity remained significant (β = –.28, p = .002), and the indirect effect through alexithymia was also significant (β = –.32, p < .001), indicating partial mediation. The overall model demonstrated good fit (χ²/df = 2.34, CFI = 0.97, RMSEA = 0.058). The findings underscore the critical role of emotional awareness in reducing interpersonal sensitivity, both directly and through the mediating influence of alexithymia. Enhancing emotional processing skills may serve as an effective target for interventions aimed at improving social functioning and emotional well-being.